Navigating the complexities of bilateral facial nerve palsy: A case report - Caisha Nivenia Moses; Wan Syahmi Bin Wan Mohamad; Kamarul Aryffin Bin Baharuddin; Mohamad Masykurin Bin Mafauzy; Mohd Faiz Bin Mohd Shukri (Turkish Journal of Emergency Medicine)
A 32-year-old male presented with a 2-week history of progressive bilateral facial weakness, initially diagnosed as unilateral Bell’s palsy. Upon development of bilateral symptoms, further investigations revealed normal hematological, biochemical, and imaging results, ruling out common infectious and autoimmune causes. Electromyography and nerve conduction studies were normal, and lumbar puncture results excluded Guillain–Barré syndrome. The patient was ultimately diagnosed with idiopathic bilateral facial nerve palsy (FNP) after exhaustive exclusion of other etiologies. Treatment with corticosteroids led to symptomatic improvement. This case underscores the importance of a systematic approach in diagnosing rare presentations of FNP and highlights the favorable prognosis with appropriate management.